2022
DOI: 10.1126/sciadv.abj5473
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic detection and reversal of myocardial ischemia using an artificially intelligent bioelectronic medicine

Abstract: Myocardial ischemia is spontaneous, frequently asymptomatic, and contributes to fatal cardiovascular consequences. Importantly, myocardial sensory networks cannot reliably detect and correct myocardial ischemia on their own. Here, we demonstrate an artificially intelligent and responsive bioelectronic medicine, where an artificial neural network (ANN) supplements myocardial sensory networks, enabling reliable detection and correction of myocardial ischemia. ANNs were first trained to decode spontaneous cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…There are now several studies investigating the potential of closed-loop VNS for treating cardiovascular conditions (Ganzer et al 2022 ; Tosato et al 2006 ; Ottaviani et al 2022 ; Ferrari et al 2011 ). For instance, closed-loop stimulation in a porcine model used the RR interval to power VNS parameters, with physiological changes being maintained up to a few minutes (Tosato et al 2006 ).…”
Section: Vns For Treating Cardiovascular Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are now several studies investigating the potential of closed-loop VNS for treating cardiovascular conditions (Ganzer et al 2022 ; Tosato et al 2006 ; Ottaviani et al 2022 ; Ferrari et al 2011 ). For instance, closed-loop stimulation in a porcine model used the RR interval to power VNS parameters, with physiological changes being maintained up to a few minutes (Tosato et al 2006 ).…”
Section: Vns For Treating Cardiovascular Conditionsmentioning
confidence: 99%
“…Myocardial ischemia is involved in several cardiovascular conditions, where there is a prolonged imbalance of myocardial oxygen supply and demand (Buja 2005 ). One recent study has demonstrated the feasibility of providing closed-loop VNS during myocardial ischemia events triggered by a machine learning model (Ganzer et al 2022 ). In a subset of experiments, myocardial ischemia was induced by a high dose infusion of catecholamines leading to correlates of myocardial ischemia, including ST segment depression and arrythmias.…”
Section: Vns For Treating Cardiovascular Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic detection and reversal of myocardial ischemia using an artificially intelligent bioelectronic medicine (Ganzer et al 2022) This research is a proof-of-concept of an Artificial Neural Network (ANN) supplementing the Myocardial Sensory Networks in reliably detecting Myocardial Ischemia through the decoding of cardiovascular pathophysiological features along with the reversal of the Myocardial Ischemia by ANN-controlled Vagus Nerve Stimulation (VNS).…”
Section: Cardiopulmonarymentioning
confidence: 99%
“…With the rapid growth and development of big data, 1,2 artificial intelligence, 3–5 Internet of Things (IoT), 6–8 and cloud computing 9 in recent decades, the agriculture field has undergone a radical transformation and entered the era of smart agriculture. While traditional agriculture mainly analyzes and summarizes the growth of crops through visual inspection or working experience, smart agriculture mainly monitors information in agricultural production activities, such as pH, environmental temperature, and humidity in real‐time through distributed sensors 10–15 .…”
Section: Introductionmentioning
confidence: 99%